THE EFFECT OF SCHOOL CULTURE, LEARNING INTEREST, AND LEARNING MOTIVATION ON NATURAL SCIENCE LEARNING OUTCOMES - Gusti Ayu Agung Purnadewi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the effect of school culture, learning interest, and learning motivation on natural science (IPA) learning outcomes for fifth-grade elementary students in cluster IV. The research is ex-post-facto research. The research sample is 196 students. The data collection methods used are the questionnaire method and document study. Data analyses used are multiple regression and partial correlation. Based on the research that has been conducted, it is concluded that 1) there is a significant effect of school culture on natural science (IPA) learning outcomes for fifth-grade elementary students at Cluster IV in Tabanan with a percentage of 42.1% and an effective contribution of 20.7%, 2) there is a significant effect with a percentage of 44.4% and an effective contribution of 18.5%, 3) there is a significant effect with a percentage of 44.1% and an effective contribution of 17%, and 4) there is a significant effect of school culture, learning interest, and learning motivation on natural science (IPA) learning outcomes for fifth-grade elementary students in Tabanan with a percentage of 56.2%.Â Â